Professionele geheimhouding - H. C. Buckle; L. Lundie; I. Treadwell (AOSIS, 1996)
Confidentiality is a "sensitive" subject known to all professional nursing personnel. The perception of confidentiality in nursing students was determined during a research project. Some responses were surprising. The surprises were mostly due to the fast development in the medical and technology fields. These findings proved to be of significance in that guidelines for confidentiality are not up to date with the developments in these fields. These guidelines should be revised or rewritten to bring them up to date and help the professional nurse in decisions on aspects concerning confidentiality.